Analysis of the Demographic Status of Diabetes Mellitus Patients in Participation in the Non-Communicable Disease Management Program - Ricko Dwi Haryanto; Lilis Rohayani; Alfina Putri Zahra (GLOBAL HEALTH SCIENCE GROUP, 2024)
NCD (Non-Communicable Diseases) activities support the proactive management of DM. This activity includes medical consultation, group education, home visits and health screenings for participants, and health education and counselling. Diabetes can be controlled using serious attention from all parties to improve the patient’s quality of life. So, NCDs (Non-communicable diseases) effectively improve the status of patient self-health maintenance. Objective to analyse the demographic status of diabetic Mellitus patients using the NCD (Non-Communicable Disease) Management program at the Nagrak Health Center, Cianjur Regency Correlative descriptive research method with a cross-sectional approach. A sample of 330 patients was taken using the random stratified sampling technique conducted in September 2023. The demographic status of the age group is related to the p-value (<0.001) on the level of utilisation of NCD (Non-Communicable Diseases) services in the Working Area of the Nagrak Health Center, Cianjur Regency by obtaining from 307 respondents with productive age to pre-elderly (37-59 years), there are 218 people (71%) whose utilisation rate of prolanis services is high, while from 23 respondents with elderly age up to high-risk elderly (60-80 years old), there are seven people (30.4%) whose utilisation rate of NCD (Non-Communicable Diseases) services. Factors affecting the coverage of participation of patients with diabetes mellitus in the NCD (Non-Communicable Disease) program are age and gender.